Highly Reversible Plating/Stripping of Porous Zinc Anodes for Multivalent Zinc Batteries. Issue 14 (27th October 2020) - Ko, Jesse S.; Bishop, Kelly; Seitzman, Natalie; Chen, Bor-Rong; Toney, Michael F.; Nelson Weker, Johanna
Abstract : Zinc continues to garner immense interest due to its versatility as an anode material in several configurations utilizing either alkaline or mild-pH electrolytes. Current research on using mild-pH electrolytes has improved the rechargeability aspect of Zn-based batteries since Zn 2+ is solely utilized for plating/stripping of Zn. Several studies have incorporated Zn metal foils, yet, dramatic improvements can be achieved by expressing Zn as a porous structure. Herein, we use a quasi-pulsed electrodeposition process to prepare a conformal Zn coating onto 3D porous copper foam. By tuning the electrodeposition parameters, we achieved an optimal Zn coating that undergoes reversible plating/stripping when tested in symmetric Zn cells, which supported a low overpotential of ∼60 mV for up to 100 cycles. We further investigated changes in the surface morphology by studying the Zn surface of both foil and 3D structure using scanning electron microscopy and X-ray micro-computed tomography. Both techniques showed that the Zn foil undergoes dramatic alterations at the surface, which results in inhomogeneous deposition of Zn, whereas the 3D form exhibited minimal changes. Lastly, we paired both Zn foil and 3D Zn with vanadium oxide and demonstrated that the porous structure supports high rate capability and high specific capacity.